A Bibliometric Analysis of Employee Turnover Intention among IT Sector Employees - Narwaria, Trapati; Dwivedi, Rajiv; Vashisht, Anil; Mishra, Apoorva; Saxena, Pratiksha; Gupta, Vivek; Singhal, Abhishek; Raghuwanshi, Sandeep (International Review of Management and Marketing, 2024)
Employee turnover is an important problem in the IT sector. However, there are still few comprehensive discussions on the current trends in employee turnover research. This study aims to comprehensively investigate relevant literature from 2019 to 2023 by bibliometric analysis to facilitate detailed exploration. The study has collected many academic documents and provided a comprehensive overview of recent research landscapes. Using the Scopus database, we used library analysis to examine the publication on employee turnover intentions between 2019 and 2023. The results showed a significant increase in research on turnover intentions, which highlighted their continued relevance in organizational research. In addition, the study identified and mapped a group of academic research focusing on employee turnover intentions, job satisfaction, employee management, and employee turnover. Key themes, influential works, and outstanding contributions were highlighted, showing the main contributors and key publications in this area. The information obtained from this study provides a valuable basis for future research and guides researchers to the most important research areas. The recommendations proposed will contribute to the development of effective retention strategies and promote better working conditions, ultimately contributing to the success and well-being of organizations and employees.